Pengaruh Pengetahuan, Sikap dan Motivasi Perawat Terhadap Pelaksanaan Keselamatan Pasien pada Unit Rawat Inap Rumah Sakit Umum Daerah Sekayu - Nora Aminayanti; Rokiah Kusumapradja; Muhammad Arrozi (Syntax Corporation Indonesia, 2021)
Patient safety concerns within healthcare organizations have come to the attention of the world and the health world responded with great efforts to address the problem. The level of knowledge of health workers about Patient Safety, motivation and attitude are internal factors that are very influential. To be able to realize the application of patient safety in hospitals is strongly influenced by the role of human resources service providers. Human Resources has the largest population in hospitals compared to other personnel and has the longest time of direct contact with patients is nurses. Therefore, the researchers conducted this study with the aim to analyze the Influence of Knowledge, Attitudes and Motivation of Nurse Work on the Implementation of Patient Safety in Inpatient Installation of Sekayu Regional General Hospital on 105 nurses in hospitals using multiple linear regression analysis. Data collection techniques use primary data questionnaire using 5 scales or likert scales. The results of the study obtained: (1) knowledge, attitudes and motivations have a simultaneous effect on the implementation of patient safety; (2) knowledge has a significant effect on the implementation of patient safety and has a positive influence; (3) attitudes have a significant effect on the implementation of patient safety and have a positive influence; (4) motivation has no significant effect on the implementation of patient safety. Attitudes are variables that have the most influence on the implementation of patient safety. This indicates that nurse foster care needs to be given more attention to the implementation of patient safety in hospital Sekayu, while knowledge and motivation become supporting variables for the variable attitude of foster care nurses in carrying out patient safety efforts.